Factibilidad para la creación de una microempresa de carpintería metálica en la ciudad de Nueva Loja provincia de Sucumbios, periodo 2012 - Chiriboga Cajamarca, José Adrián (2012)
An investment project is carried out after making various stages of study and analysis, these issues include decisions that the investor must do to make your venture will be translated into something that is equally productive and profitable, for this reason, research which took place in the city of Nueva Loja, considered the following points: Research Objectives: • Determine the supply and demand for the creation of microenterprises in metalwork. • Perform technical, economic and financial support for the creation of microenterprises in metalwork in the city of Nueva Loja. • Establish the profitability and feasibility of microenterprise. • Identify the environmental impact that would generate the micro in the area of influence. To record the results of research formats used population surveys and the area of competition for these products, would ponder about prices, purchase Amount frequency and quality. The initial fixed investment of the project is $ 28,710,00 operating costs are $ 118,647.82 for the first year, while projected revenues amount to $ 128,550, the balance point for micro-enterprises is 596 900 windows and doors units. The income statement has a net utility $ 6,312.64 in the first year. The financial study determined that the benefit cost is $ 5.37, which is good for investment, the capital recovery period is expected in the first year, so the project is profitable, especially if one considers year zero that negative investment is $ 35,178.53, it was with an interest rate of 10%, resulting in a positive NPV of $ 751,075.50 and $ 12,096.07 negative NPV. While the Internal Rate of Return (IRR) is 488%, which means that the project is attractive. The capital recovery period is 1 year, 5 months and 15 days, parameters determined by the corresponding study, so it is concluded that the project is profitable.